The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12034-015-1014-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides

Abstract: A series of thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2methyl-1,4-benzene (BHBOMB) and aliphatic dicarboxylic acid chlorides were investigated. All these polyesters were synthesized by interfacial polycondensation method and characterized by differential scanning calorimetry and wide-angle X-ray diffractometer. These polyesters consist of BHBOMB as a mesogenic diol and aliphatic diacid chlorides were used as flexible spacers. The length of oligomethylene units in polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The incorporation of methyl substituent on hydroquinone central moiety of triad mesogen unit resulted in lower isotropisation temperature with respect to the similar number of methylene units. 18 In short, crystal to liquid crystal transition temperatures of unsubstituted hydroquinone based polyesters were higher than those of the methyl and chlorohydroquinone based polyesters. The trend of crystal to liquid crystal transition temperature of polyesters based on hydroquinone is as follows: H > Me > Cl.…”
Section: Substitution Effectsmentioning
confidence: 92%
See 2 more Smart Citations
“…The incorporation of methyl substituent on hydroquinone central moiety of triad mesogen unit resulted in lower isotropisation temperature with respect to the similar number of methylene units. 18 In short, crystal to liquid crystal transition temperatures of unsubstituted hydroquinone based polyesters were higher than those of the methyl and chlorohydroquinone based polyesters. The trend of crystal to liquid crystal transition temperature of polyesters based on hydroquinone is as follows: H > Me > Cl.…”
Section: Substitution Effectsmentioning
confidence: 92%
“…16 In our previous papers, we reported the synthesis and characterization of thermotropic liquid crystalline polyesters derived from hydroquinone and methyl hydroquinone-based rigid rod diols as mesogenic units and aliphatic dicarboxylic acids as flexible spacers. 17,18 The present investigation demonstrates synthesis and characterisation of TLCP derived from bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene (BHBOCB) as mesogenic moiety and aliphatic diacid chloride as flexible spacer. Flexible spacer was inserted into the backbone of the rigid polymer to dissociate the greater order of the main-chain and decouple the motion of mesogenic moiety from polymer backbone.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In these polymers, an exothermic peak appears before melting transition, which seems to be related to crystal to crystal transition resulted from different crystalline polymorphs. 14 The liquid crystalline range ( of the poly(ester-amide) derived from terephthalic acid monomer is broader than compared to the poly(ester-amide) derived from other monomers. This may be due to effective molecular packing by coplanar geometry.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Liquid crystalline thermosets are a class of materials that combine properties typical of thermotropic liquid crystalline polymers with those of conventional thermosets. Mulani et al [12] observed very large mesophasic stability for new liquid crystalline polyesters consisting of bis-(4hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides [12]. Applications of liquid crystal thermosets include the advanced adhesives, new matrix materials for composites and variety of applications for microelectronics industry.…”
Section: Introductionmentioning
confidence: 99%